2016
DOI: 10.1088/1757-899x/133/1/012056
|View full text |Cite
|
Sign up to set email alerts
|

The effect of erosion and abrasion on surface properties of composite resin

Abstract: View the article online for updates and enhancements. Related contentComputer Simulation of Stress-Strain State of Pipeline Section Affected by Abrasion Due to Mechanical Impurities P V Burkov, R G Afanas'ev and S P Burkova -Fatigue variation of surface properties of silumin subjected to electron-beam treatment S V Konovalov, K V Aksenova, V E Gromov et al. Abstract. The aim of the study was to evaluate the surface roughness of two commercial composite resins submitted to erosive attack, to abrasive wear and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The first stage in erosive degradation is water absorption, which can further infiltrate the resin matrix at the interface with fillers or other defects, compromising their reinforcing effects. Also, factors like the cross-linked nature of the resin matrix and the solvent sorption uptake directly affect composite resin degradation [50]. Previous studies showed that the increase in composite resin roughness in acidic solutions is probably due to their softening surface, which leads to the leaching of the resin components and the displacement of the filler particles [51].…”
Section: Discussionmentioning
confidence: 99%
“…The first stage in erosive degradation is water absorption, which can further infiltrate the resin matrix at the interface with fillers or other defects, compromising their reinforcing effects. Also, factors like the cross-linked nature of the resin matrix and the solvent sorption uptake directly affect composite resin degradation [50]. Previous studies showed that the increase in composite resin roughness in acidic solutions is probably due to their softening surface, which leads to the leaching of the resin components and the displacement of the filler particles [51].…”
Section: Discussionmentioning
confidence: 99%
“…Composite resins have gain popularity during the time and now are the most used materials for direct restoration. Unfortunately, in oral environment, these materials are exposed to different chemical and physical aggressions [1,2] and are prone to degradation [3]. Dental practitioners have claimed some disadvantages of these materials like polymerization shrinkage, microleakage, postoperative sensitivity, poor marginal adaptation, sensitive technique for placement, difficult handling.…”
mentioning
confidence: 99%